Educação ambiental na disciplina de Geografia: uma análise dos PCN s e da produção acadêmica em Geografia - Amorim, Adriana Barbosa (2015)
This work presents the environmental issues within the geographical science by analyzing the NCP's and its application in basic formal education (third and fourth cycle / key II). Understanding the Environmental Education as a first step to take when you want to mobilize people for actions related to environmental preservation. Since the current debates the man stands as questioning about the way society has been linked with nature, and discusses how the capitalist mode of production contributes to this destructive scenario between man and nature. For this to happen formal education must have an effective role for the understanding of environmental issues, so it is an analysis of academic papers in the field of Geography so far developed that address this issue. And one realizes that still needs better preparation of teachers and academic depth, that is, understanding the articulation of a field specific knowledge of geographical science curriculum proposal of the Parâmetros Curriculares Nacionais (PCN) in Geography. Especially taking into account that new concepts emerged due to the fervor of environmental discussions and contradictions that bring these terms, raises the researcher / teacher the need to prepare to deal with these issues so that they can discuss the contradictions that some environmental concepts bring invalidate the understanding and solutions to environmental issues that geography has been doing. To do so will consider the NCP's geography of elementary school (third and fourth cycle), and the tools that the course in its theoretical arsenal to deal with this issue. Where we found that the environmental education teaching in geographical science is likely to happen, despite all the issues surrounding the subject from the teacher's knowledge of the discussions involving this knowledge, beyond the knowledge of the tools that discipline Geography has to form a critical / reflective thinking on the subject